2019
DOI: 10.1155/2019/5632145
|View full text |Cite
|
Sign up to set email alerts
|

Smart Switching Bilateral Filter with Estimated Noise Characterization for Mixed Noise Removal

Abstract: Traditionally, several existing filters are proposed for removing a specific type of noise. However, in practice, the image communicated through the communication channel may be contaminated with more than one type of noise. Switching bilateral filter (SBF) is proposed for removing mixed noise by detecting a contaminated noise at the concerned pixel and recalculates the filter parameters. Although the filter parameters of SBF are sensitive to type and strength of noise, the traditional SBF filter has not taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…In 43 the Robust Outlyingness Ratio, which is a local statistic capable of efficiently detecting outliers, was used to remove impulsive noise disturbances and then the NLM filter was applied, adapting its parameters to the remaining noise characteristic. In 44 the impulses were first detected by sorted quadrant median vector 28 and the unfiltered noise was smoothed out by BF, which parameters were tuned on the basis of an estimation of the mixture noise composition and its intensity. The method of mixed noise reduction described in 45 firstly detects the impulses and the subsequent stages use filters utilizing the PCA technique.…”
Section: Related Workmentioning
confidence: 99%
“…In 43 the Robust Outlyingness Ratio, which is a local statistic capable of efficiently detecting outliers, was used to remove impulsive noise disturbances and then the NLM filter was applied, adapting its parameters to the remaining noise characteristic. In 44 the impulses were first detected by sorted quadrant median vector 28 and the unfiltered noise was smoothed out by BF, which parameters were tuned on the basis of an estimation of the mixture noise composition and its intensity. The method of mixed noise reduction described in 45 firstly detects the impulses and the subsequent stages use filters utilizing the PCA technique.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, they proposed a trilateral smoothing algorithm to solve this challenge. Langampol, et al [104] suggested to improve the performance of switching bilateral filter by introducing a domain weight pattern.…”
Section: Bilateral and Trilateral Filteringmentioning
confidence: 99%
“…However, it is more difficult to remove mixed noise due to the complex distribution of the noise. Researchers have developed many effective algorithms [23–32]. Xiao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [26] combined an adaptive directional weighted mean filter with an anisotropic diffusion model for mixed noise removal. A smart switching bilateral filter (SBF) was proposed [27] to compensate for the shortcomings of the traditional SBF filter. In [28],the transfer learning (TL) approach was adopted to obtain a map between noisy observations and noise-free images.…”
Section: Introductionmentioning
confidence: 99%